Propuesta de diseño de una planta industrial para la extracción de aceite de palmiste en la empresa ROCZO S.A. - Meza Moran, Erick Jordan (2018)
SA, located in the El Lechugal site, in the Quevedo canton, has as an activity the production of activated carbon a base of the husk of the palm nut African, to be used a palm oil extractor with a method of extraction in a single stage, complying with national standards for its use and standards for the safety and occupational health of workers. In the development of the work the qualities of the product are detailed, the amount of raw material to be processed. Once the capacity of the plant, the development of a technical study that represents a satisfactory performance for the design of the plant. In the analysis of material flow and mass balance, the point of origin, the volumes, the causes of the waste, the emissions produced and the weaknesses of the production process are identified. The parameters for the oil production allow to control the behavior of the stock of material, labor, and machines and to comply with national standards to obtain a quality product. Finally, the security measures required for the process are determined, as well as the workers' safety and health regulations, which allow for the wellbeing of the employees. Key words: Flow analysis, Parameters to be monitored, Health and safety regulations for workers, Mass balance.